Do Institutions Affect Citizens' Selection into Politics? - Thomas Braendle (University of Basel, Center of Business and Economics (WWZ), 2013)
Traditional political economy has paid primary attention to the structuring of the principal-agent relationship between citizens and politicians and the role of competition and institutions in disciplining political agents. However, as the electoral control of politicians and the credibility of policy commitments are limited, this perspective needs to be complemented with an economics of political selection that takes into account the quality of those elected to political office. We review the emerging literature which investigates institutional conditions that impact the selection of politicians. We discuss pay in politics, electoral rules, institutions enhancing transparency in politics, and institutions which govern dual office holding in different branches of government. We argue that further comparative analyses are essential in order to gain an improved understanding of the impact that institutions have on political outcomes, not only via the channel of accountability, but also via the channel of selection.
Keywords: D72; D73; H11; 330; political selection; electoral rules; incompatibility; citizen candidate model; Partizipation; Wahlverhalten; Wahlsystem; Neue politische Ökonomie; Theorie